长住新加坡的马来西亚华人语码转换和混用的特征研究 = An investigation of the features of code switching and code mixing by Malaysian Chinese residing in Singapore - 赵洁莹 Chew, Kiat Yin (2011)
许多马来西亚人长期居住在新加坡，他们的语言习惯在一定程度上会受到新加坡语言环境的影响。不过普遍上来说，这些马来西亚华人并没有完全适应或养成新加坡华语式的交流方式和习惯，比如他们并不像新加坡人那样常做语码转换和混用；但是，值得注意的是，有一部分马来西亚华人已将这种中英语码夹杂的表达方式内化成了自己的说话习惯。鉴于此，本研究针对在新加坡长期居住的马来西亚华人的语码转换和语码混用现象做了实证调查研究。此项研究共分两个部分，第一部分是通过收录三十四名在新加坡居住了一个月到二十八年的马来西亚华人的语音材料，了解他们的语码转换结构类型、语码混用之嵌入词汇的词性以及探讨影响马来西亚华人的语码转换和混用频率的各种因素。第二部分则针对四名在新加坡住满七年并且非常习惯进行语码转换或混用的马来西亚华人的语音材料加以分析，进而探究男女被试是否分别在谈论某种类型的话题时会出现较多的语码转换或混用，从而探讨马来西亚华人自身的语言在新加坡的语言环境中所受到的影响和改变，以及他们改变后的语言又与新加坡的语言模式有何不同。With long periods of settlement in Singapore, many Malaysian Chinese’s usual practice of their language have been influenced by Singapore’s language speaking environment. In general, not all Malaysian Chinese have fully adopted and cultivated the habit of code switching and mixing as Singaporean’s do. However, a small group of Malaysian Chinese have been found to have been developed the habit of making Chinese–English code mixing in their daily communication. Therefore, we carried out an empirical investigation to study the phenomenon of code switching and code mixing of Malaysian Chinese speakers who have resided in Singapore for a certain period of time. The investigation was done in two parts. The first part was done by interviewing 34 Malaysian Chinese who have been staying in Singapore with duration from 1 month to 28 years. The recorded conversations of their spoken language were transcribed and searched for the forms of their code switching and the word classes of the words used in their code mixing sentences. The variables that affect their frequency of code switching and code mixing were analysed. The second part was pin-pointed onto 4 Malaysian Chinese speakers who have been staying in Singapore for 7 years and have been significantly affected by Singaporeans language speaking habit.